Graphic roles in constructing an appealing packaging of traditional health herbal products / Hanafi Mohd Tahir, Mohd Khairul Azahari Abdul Rani and Syahrul Nizam Shaari - Tahir, Hanafi Mohd; Abdul Rani, Mohd Khairul Azahari; Shaari, Syahrul Nizam (Research Management Institute (RMI), 2011)
Nowadays lifestyle, consumers tend to obtain health herbal's products as supplements. Varieties of brand names with range of packaging design exceptional. Even though there are varieties and abundance in the market, majority of the consumers self-assured to utilize imported health herbal products. Undeniably, imported health products monopolize the Malaysian market. Nevertheless both of the products guarantee and represent the same benefits of energy booster, "for health and for energy". Consumer will purchase a product if it's consider safe to use even though was first time purchasing it. Self-service environment becomes a trend on selling products. Packaging has become a media and it has ability to communicate. This research will include a review on the roles of graphics towards packaging industries, traditional and imported health herbal products (capsule based) in Malaysian market. Through this research, result showed that most respondents believe imported health herbal products are popular among the consumers choice. In fact imported health herbal products approaches in promoting their products were more successful than those of traditional health herbal companies. Researcher found that the majority of the consumers in Malaysian market are brand oriented. Most Malaysian consumers feel safe, confident to use imported health herbal products. Graphic elements on the packaging design showed results that it affect the buying decision. It is also strongly noted that product promises of traditional health herbal product on the packaging are one of major factors that attract consumer because consumer will feel save to use it Other factors to be taken into consideration are aggressive promotions and impressive advertising. In fact, it will help traditional health herbal products valuable and good investments to the government industry.